Autoimmune (IgG4-related) pancreatitis and cholangitis - Chari, Suresh T. (Springer New York Imprint: Springer, 2013)
Autoimmune (IgG4-related) Pancreatitis and Cholangitis reviews the breadth of clinical, imaging, histological, laboratory, and imaging features associated with IgG4-associated systemic disease, especially AIP and IAC. Written by experts in their fields, each chapter includes an overview of existing data as well as the most up-to-date scientific information and emerging data. The book also addresses areas of uncertainty and controversy, briefly highlighting clinical and research needs relative to the respective topic. Comprehensive and easy to use, Autoimmune (IgG4-related) Pancreatitis and Cholangitis is a valuable resource for physicians who deal with or are interested in these complex disease processes, including gastroenterologists, hepatologists, and surgeons.